Iddah Period Reviewed from the Qur'an and Compilation of Islamic Law - Moch Andika Rajeswara (Penerbit Hellow Pustaka, 2025)
Iddah is a period of waiting for a woman after the fall of talaq from a husband or due to death. Refrain from remarrying until the end of the iddah period. The purpose of this study is to understand how a wife's iddah after divorce. This research includes literature research that uses descriptive analytical as a method. This paper aims to provide a comprehensive analysis of the discussion of iddah in the Qur'an and the Compilation of Islamic Law, along with the types and axiological values in it where iddah is part of a woman's marriage journey after a divorce.